The Silk Road and the Turkish world - Toirova Dilnoza Gayratovna (Periodica Journal, 2025)
The connection between the Silk Road and the Turkish world occupies an important place in the history of mankind. The Silk Road has served as the main route of trade and cultural exchange between East and west since ancient times. Through this path, not only goods, but also ideas, religions, art and science spread. Turkish peoples, on the other hand, were central participants in this route, and their culture, economy, and politics were closely linked to the Silk Road.
Keywords: culture, art, science, communication, literature, art, style, cooperation, directions